Microplastics in the Syr Darya River Tributaries, Uzbekistan - Frank, Yuliya A.; Khusanov, Alijon; Yuldashov, Mansur; Vorobiev, Egor D.; Rakhmatullina, Svetlana N.; Rednikin, Aleksey; Tashbaev, Sherzodbek; Mamatkarimova, Sarvinoz; Ruchkina, Kristina; Namozov, Sirojiddin; Turaev, Laziz; Sobirov, Jobir; et al. (Water)
The objective of the study was a pre-screening of the microplastic (MP) content in surface water and benthic sediments of Kara Darya and Chirchiq rivers, the first-order tributaries of the Syr Darya River (Uzbekistan). For the first time, surface water and benthic sediment samples were taken from this region, and quantitative screening of MPs 0.15–5.00 mm in size was performed. A combined visual and μRaman-based methodology was used to quantify and characterize artificial polymer microparticles from the surface water and bottom sediments of two rivers. The average abundance of MPs in the Kara Darya River and Chirchiq River waters was found to be 4.28 ± 0.09 and 0.95 ± 0.36 items per m3, and that in benthic sediments attained 244 ± 28.9 and 333 ± 11.5 items per kg of dry soil, respectively. MP concentration in surface water and benthic sediments of the Kara Darya River significantly exceeded (p-value < 0.01) that in the Chirchiq River. Microfibers were most abundant; the proportion of MP fibers in the water of the Kara Darya and Chirchiq rivers amounted to 89 and 95%, respectively, and that in benthic sediments of the rivers was 86 and 84%, respectively. The dominance of microfibers may indicate the route of entry to the rivers through domestic wastewater treatment plant discharges. The polymer microparticles in the surface water and benthic sediments of the Kara Darya and Chirchiq rivers were mainly represented by polyethylenterephtalate (PET), which accounted for half of all MPs detected in the Kara Darya River. Microparticles of textile origin were particularly abundant in the Kara Darya River, where viscose and nylon fibers were also found, which suggests the leading role of synthetic textiles in the pollution. The reported data are the first experimental evidence of MP pollution of the Syr Darya tributaries, but the distribution and circulation of MPs in surface water in Central Asia requires further comprehensive studies.